ANALYSIS OF SURVIVAL STRATEGIES OF SPECIES ALLIUM L. IN THE RUSSIAN CAUCASUS - V. A. Chadaeva; S. H. Shhagapsoev (Юг России: экология, развитие, 2016)
The aim. The main objective of this work is to analyze the survival strategies of 20 species of the Allium genus in the Russian part of the Caucasus (Kabardino-Balkaria, Karachay-Cherkessia, North Ossetia, Ingushetia and Dagestan).Methods. Life strategies of wild onions have been considered within the concept of L. Ramensky and J. Grime, using the most significant feature markers at the organismal and population-ontogenetic levels.Results. Studies have shown that all studied species are characterized by the mixed types of strategy with the presence of the patient strategy component. Often, even closely related morphologically similar species have a different set of mechanisms of stability when growing in similar conditions. Accordingly, the features of the formation of life strategies can be used as diagnostic taxonomic characters in distinguishing morphologically similar species. It has also been shown that under the effectiveness of life strategy it is appropriate to consider the maintenance of stability of coenopopulations as in stable conditions or gradual changes in the ecological and phytocoenotic environment, coenopopulations are resistant thanks to a particular component of survival strategies. Accordingly, when assessing the status of species in nature it is crucial to take into account the peculiarities of its life strategy, which involves carrying out complex investigations.Main conclusions. Thus, the analysis of plant species survival strategies provides a large amount of information important in differentiating morphologically similar species, determining their state in nature, identifying the functional role of species in ecosystems and their indicator values in assessing the degree of resilience of ecosystems as a whole.